2022
DOI: 10.1080/17445647.2022.2095935
|View full text |Cite
|
Sign up to set email alerts
|

Jezero crater, Mars: application of the deep learning NOAH-H terrain classification system

Abstract: We applied a deep learning terrain classification system, the 'Novelty or Anomaly Hunter -HiRISE' (NOAH-H), originally developed for the ExoMars landing sites in Oxia Planum and Mawrth Vallis, to the Mars 2020 Perseverance rover landing site in Jezero crater. NOAH-H successfully classified the terrain in four HiRISE images of Jezero even though the landforms in the Jezero study area were slightly different from those in the training dataset. We mosaicked the NOAH-H classified rasters and compared them with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This highlights some implications for the interpretation of similar spectral signatures elsewhere on Mars, as fine soils tends to have an overall composition common to different locations on the planet (Cousin et al, 2015). Wright et al (2022) demonstrated that the surficial covers of Máaz and Séítah are significantly different, with the Máaz surface being mostly composed of scarce bedrock exposures and soils and the Séítah surface of scarce bedrock exposures and large sand ripples. We showed that the sand dunes that are widely covering the Séítah formation seem to be composed of material sourced from the local bedrock.…”
Section: Orbital Data Sets: Bedrock Exposures Versus Soils Signaturesmentioning
confidence: 85%
See 1 more Smart Citation
“…This highlights some implications for the interpretation of similar spectral signatures elsewhere on Mars, as fine soils tends to have an overall composition common to different locations on the planet (Cousin et al, 2015). Wright et al (2022) demonstrated that the surficial covers of Máaz and Séítah are significantly different, with the Máaz surface being mostly composed of scarce bedrock exposures and soils and the Séítah surface of scarce bedrock exposures and large sand ripples. We showed that the sand dunes that are widely covering the Séítah formation seem to be composed of material sourced from the local bedrock.…”
Section: Orbital Data Sets: Bedrock Exposures Versus Soils Signaturesmentioning
confidence: 85%
“…Wright et al. (2022) demonstrated that the surficial covers of Máaz and Séítah are significantly different, with the Máaz surface being mostly composed of scarce bedrock exposures and soils and the Séítah surface of scarce bedrock exposures and large sand ripples. We showed that the sand dunes that are widely covering the Séítah formation seem to be composed of material sourced from the local bedrock.…”
Section: Discussionmentioning
confidence: 99%